Checking... A fear of dark water - Craig Russell (London : Arrow, 2012)
"Jan Fabel has returned to the Hamburg murder squad to track down a horrifying killer. Just as a major environmental summit is about to start in Hamburg, there is a massive storm hitting the city. After the flood waters recede, a headless torso is found washed up. At first Jan believes this may just be another victim of a serial rapist and murderer who is stalking his victims through social network websites, then Read more...